PERANCANGAN STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) DALAM MENDORONG KONVERSI PENGGUNAAN PRODUK BY.U BY TELKOMSEL SEBAGAI COPYWRITER - Nadya Syafiqa; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
by.U is a digital mobile service launched by Telkomsel, primarily targeting Generation Z andyoung, digitally active users. However, by.U usage among high school and vocational schoolstudents in Semarang remains relatively low. A survey of 814 students from four schoolsaffiliated with Telkomsel's educational platform, Skul.id, found that only 46 students, orapproximately 5.7%, were active by.U SIM card users. Furthermore, the survey also showedthat the perceived risk of the service remains quite high, at 52.2%, while purchase intentionremains at 20.8%. To address these issues, an integrated marketing communications campaignwas designed through the "by.U On The Move" and "by.U Inter-School Digital Challenge"programs. This campaign employed an Integrated Marketing Communication (IMC) approach,utilizing various communication channels such as media relations, social media marketing,influencer marketing, and event marketing. The communication strategy aimed to driveaudiences through the stages of attention, interest, desire, and action, in accordance with theHierarchy of Effects model in marketing communications.The campaign implementationdemonstrated a change in audience response. Perceived risk decreased from 52.2% to 19.5%,while purchase intention increased from 46 to 118 students at the target schools. During thecampaign, the author served as a copywriter responsible for crafting communication messagesand developing campaign content.